Eosinophil-to-Neutrophil Ratio and Eosinophil Count as the Potential Biomarkers for Differentiating Breast Cancer Stage: A Retrospective Study - Phey Liana; Priscilla Yukiko Djamili; Yolanda Paulina Waruwu; Nur Qodir; Kemas Ya’kub Rahadiyanto; Dwi Handayani; Tungki Pratama Umar (Biomedical and Biotechnology Research Journal)
Background: Early detection of breast cancer (BC) is a very important matter in clinical settings to reduce tumor burden and improve patients’ outcome. Some hematological parameters either single or in combination as inflammatory hematological ratio may provide essential information to differentiate BC patients from healthy controls and based on disease progression. These markers demonstrated high usability particularly in resource-limited and cost-limited landscape. This study sought to determine comparative ability of hematology-related laboratory parameters across early- and late-stage BC. Methods: This cross-sectional study utilized the medical record and laboratory data of women adult BC patients that were divided into two categories: early- and late-stage BC. Patients’ laboratory data included hematological laboratory results, leukocyte differential count, and inflammatory hematological ratios. Bivariate analysis evaluated laboratory parameters difference between early and late BC stage using the independent t-test or Mann–Whitney U-test, followed by effect size calculation. Predictive accuracy was done using the receiver operating characteristic analysis followed by sensitivity and specificity determination. All statistical analyses were performed using IBM SPSS software (version 27.0) and Medcalc (version 22.018). Statistical significance was defined at P < 0.05. Results: From 237 samples analyzed in this study, there is significant difference between early- and late-stage BC for leukocyte (7.86 ± 2.95 × 103/μL vs. 7.11 ± 1.83 × 103/μL, P = 0.047, Cohen’s D effect size = −0.267), eosinophil (3.00 [0–7.00] % vs. 2.00 [0–10.00] %, P = 0.041, r = 0.135), and eosinophil-neutrophil ratio (ENR) (0.05 [0–0.15] vs. 0.03 [0–0.14], P = 0.027, r = 0.146). However, predictive accuracy analysis only showed significant value to eosinophil (higher sensitivity) and ENR (higher specificity). Conclusions: Eosinophil-related parameters (eosinophil count and ENR) have the potential to differentiate BC patients based on the early and late stages of the disease.